What Have Become of Me: Branching Narrative and Morally Ambiguous Characters (MACs) in Detroit: Become Human and The Witcher 3 Video Games - Rayana Alif Anggoro; Satriya Muhammad Aulia Ridwan; Zakky Fawwaz Maulana Al Ghozi (EDU-KATA, 2026)
This study explores how branching narratives construct morally ambiguous characters (MACs) and influence moral reflection in video games. Focusing on Detroit: Become Human and The Witcher 3: Wild Hunt, the research investigates how player choice and narrative design shape moral identity and ethical choice. The problem addressed in this study lies in understanding how different narrative and cinematic branching and open-world structures, produce moral complexity through player interaction. Using Spradley’s (1980) ethnographic analysis combined with Krakowiak’s (2012) narrative engagement framework, the research identifies three major domains: moral dilemma, identity and transformation, and consequences of actions. The findings reveal that moral dilemmas encourage ethical self-reflection, identity transformation emerges through interactive decision-making, and consequences of actions based on accountability and emotional investment. Both games demonstrate that moral meaning in interactive storytelling is shaped by the player, blurring the line between author and audience. The study concludes that branching narratives and morally ambiguous characters form a unified system of ethical engagement, where players’ decisions not only define character identity but also cultivate deeper emotional and understanding of morality within digital play.